Induction of thermogenesis in brown and beige adipose tissues. Issue 5 (October 2015) - McMillan, Andrew C.; White, Matthew D.
<x xml:space="preserve">Abstract</x> Purpose of review The purpose of this short review paper is to summarize recent developments in the understanding of the activation, growth and function of brown adipose tissue (BAT). Recent findings Transcriptional markers for increased BAT activity and differentiation of white adipocytes to 'beige' or 'brite' adipocytes include amongst others peroxisome proliferator-activated receptor γ, cytosine-enhancer-binding protein, positive regulatory domain 16 and bone morphogenetic proteins. These markers induce uncoupling protein 1 expression in brown and 'beige' or 'brite' adipocytes which allows energy from macronutrients to be expended as heat. Acute and repeated mild cold exposures of 17–19 °C in adult humans increase BAT volume and activity and this is a novel method for increasing their energy expenditure. Emerging evidence suggests that irisin and melatonin hormones may be involved in BAT activation. Additionally, brown adipocyte stem cell therapy transplantation is a means to stimulate this increased thermogenesis from brown and 'beige' or 'brite' adipocytes. Summary Markers for increased BAT activation and for white adipocyte differentiation into beige/brite adipocytes have been identified, and these lead to an uncoupling protein 1-mediated increase in metabolic rate. Mild cold exposure and brown adipocyte stem cell transplantation are two potential strategies for inducing activation and growth of BAT for the treatment of human obesity.